Effects of hypoxic preconditioning on memory evaluated using the T-maze behavior test. Issue 1 (2nd January 2019) - Kim, Yun-Hee; Lee, Kuen-Su; Kim, Young-Sung; Kim, Yeon-Hwa; Kim, Jae-Hwan
ABSTRACT: Perioperative brain ischemia and stroke are leading causes of morbidity and mortality. Brief hypoxic preconditioning is known to have protective effects against hypoxic-ischemic insult in the brain. Current studies on the neuroprotective effects of ischemic preconditioning are based on histologic findings and biomarker changes. However, studies regarding effects on memory are rare. To precondition zebrafish to hypoxia, they were exposed to a dissolved oxygen (DO) concentration of 1.0 ± 0.5 mg/L in water for 30 s. The hypoxic zebrafish were then exposed to 1.0 ± 0.5 mg/L DO until the third stage of hypoxia, for 10 min ± 30 s. Zebrafish were assessed for memory retention after the hypoxic event. Learning and memory were tested using the T-maze, which evaluates memory based on whether or not zebrafish moves to the correct target compartment. In the hypoxic preconditioning group, infarct size was reduced compared with the hypoxic-only treated zebrafish group; memory was maintained to a degree similar to that in the hypoxia-untreated group. The hypoxic-only group showed significant memory impairments. In this study, we used a hypoxic zebrafish model and assessed the effects of ischemic preconditioning not only on histological damages but also on brain function, especially memory. This study demonstrated that a brief hypoxic event has protective effects in hypoxic brain damage and helped maintain memory in zebrafish. In addition, our findings suggest that the zebrafish model is useful in rapidly assessing the effects of ischemic preconditioning on memory.